Peran Citra Merek dalam Memediasi Pengaruh Keunggulan Produk terhadap Minat Beli Ulang Uniqlo - Hasibuan, Laila Handayani; Tarigan, Eka Dewi Setia (Universitas Medan Area, 2025)
This article aims to analyze the role of brand image in mediating the influence of product advantages on repurchase interest in Uniqlo fashion products. The problem is focused on the intense competition in the fashion industry, where product advantages and brand image are key factors influencing consumers’ decisions to make repeat purchases. To approach this problem, the study refers to theories from marketing, consumer behavior, and brand management, which emphasize the role of brand image as a mediator between product quality and customer loyalty. The data were collected through questionnaires distributed to 99 Management students from the 2022 cohort at the University of North Sumatra, selected using a purposive sampling technique, and analyzed quantitatively using Structural Equation Modeling based on Partial Least Squares (SmartPLS) with path analysis. This study concludes that product advantages significantly influence brand image, which in turn mediates the effect of product advantages on repurchase interest. In addition, brand image has a direct and significant effect on repurchase interest, indicating that improving product quality and strengthening brand image are essential strategies for enhancing customer loyalty.